Epidemiological and molecular analysis of anthrax cases of the Zhambyl region Kazakhstan in 2023 - Izbanova, Uinkul; Rysbekova, Altyn; Zhumadilova, Zauresh; Kovaleva, Galina; Tokmurziyeva, Gulnara; Abdeliyev, Bek; Yessimseit, Duman; Begimbayeva, Elmira; Umarova, Saule; Zarkymanova, Anar; Sabitova, Meruert; Yussupov, Aisazhan; et al. (Frontiers in Public Health, 2025)
BackgroundAnthrax, caused by Bacillus anthracis, continues to pose a serious zoonotic threat in endemic areas such as southern Kazakhstan. Its persistence in the environment through resilient spores facilitates prolonged transmission cycles between animals and humans.ObjectiveThis study aimed to characterize the epidemiological, clinical, and molecular features of human anthrax cases reported in the Zhambyl region of Kazakhstan during 2023.MethodsA total of 41 suspected cases were investigated, of which 19 were confirmed by culture and PCR (targeting pXO1 and pXO2). Data collection included patient demographics, exposure circumstances, clinical manifestations, and laboratory diagnostics. MLVA-31 genotyping was used to characterize B. anthracis isolates from culture-positive patients.ResultsConfirmed cases were clustered in five district localities, yielding an incidence rate of 1.55 per 100,000 population. The majority of patients were male (84.2%), with exposure primarily linked to slaughter activities (68.4%). Culture was successful in 12 of 19 confirmed cases, and all isolates were susceptible to a broad range of antibiotics, including ciprofloxacin and doxycycline. Genotyping revealed three distinct clusters: one matching the A.Br.001/002 genotype common to northeastern China and Mongolia, and two divergent clusters likely represent localized evolution of B. anthracis strains. Five previously undocumented foci of anthrax were identified, suggesting wider regional spread than previously recognized.ConclusionThe 2023 outbreak of anthrax in the Zhambyl region highlights the ongoing risk posed by B. anthracis, particularly in areas with active livestock trade and conducive environmental conditions. The genetic diversity among isolates suggests both recent transmission and deeper endemic roots. Strengthening livestock vaccination programs, improving rural surveillance, and promoting awareness among high-risk populations are critical to preventing future outbreaks.